POLITICAL COMMUNICATION STRATEGIES OF MEDAN CITY DPRD MEMBERS DURING RECESS IN THEIR ELECTORAL DISTRICT IN LABUHAN, MEDAN - Anugerah Zebua; Salman Hasibuan; Evi Enitari Napitupulu; Lola Gebri Andayati Br Sembiring (Program Pascasarjana UIN Sumatera Utara, 2026)
This study aims to analyze the political communication strategy of members of the Medan City Regional House of Representatives (DPRD) in conducting recess activities in the Constituency of Two Medan Labuhan Districts. Recess is an important constitutional mechanism for legislators to collect constituent aspirations and strengthen the relationship between the legislature and the community. This study employed a descriptive qualitative approach, with data collected through in-depth interviews, non-participant observation, and documentation. Informants comprised one DPRD member as the key informant and five constituent community members as supporting informants. Data analysis was conducted using the Miles and Huberman model. The findings reveal that the communication strategies employed include: (1) direct communication through face-to-face forums and constituent dialogue; (2) utilization of social media platforms such as Facebook, Instagram, Twitter, and official websites for disseminating information and documenting recess activities; and (3) synergy with the Musrenbang mechanism to follow up on public aspirations. Despite challenges such as the diversity of constituent characteristics and aspirations not yet fully realized, council members have developed their own approaches to maximize the effectiveness of recess activities. This study concludes that an integrative communication strategy combining direct and digital approaches is crucial to the successful absorption of aspirations during recess.